Effect of Curcumin on the Properties of Decellularized Fish Skin for Wound Healing - Ayedeh Asgari; Esmaeil Biazar; Saeed Heidari Keshel; Reza Zeinali; Mostafa Rezaei Tavirani; Azam Rahimi; Davood Zaeifi; Soheil Shokri (Journal of Medical and Biological Engineering, 2026)

Analysis of Fennel Breeding Populations Based on Distinctness, Uniformity, and Stability (DUS) Testing via Morphological Descriptors and DNA Molecular Markers - Azam Akbari; Keivan Bahmani; Murat Kazan; Ömer Faruk Bilgin; Jawed Rahimi; Ali Izadi Darbandi; Nesibe Ebru Kafkas; Salih Kafkas (Genetic Resources and Crop Evolution, 2025)
A bred plant variety is a valuable tool for enhancing crop production and total yield. Recently, our breeding team developed three high seed yielding synthetic cultivars of bitter fennel. To characterize these newly breeding populations and differentiate them from each other and their parental populations, we conducted a Distinctness, Uniformity, and Stability (DUS) assessment using morphological traits evaluated over two consecutive years, as well as 20 Start Codon Targeted (SCoT) markers. The evaluation of morphological traits revealed that, five of qualitative traits exhibited monomorphism, while two other qualitative traits displayed polymorphism. Additionally, the investigation of eight quantitative traits showcased significant diversity. The Combined Over Years Distinctiveness analysis at a 1% significance level, based on eight quantitative characteristics, indicated distinctiveness for two breeding populations, namely Early and Medium Maturity Synthetic cultivars, compared to other populations. The Combined Over Years Uniformity analysis identified that all of the breeding populations and their parental populations were uniform in terms of the measured traits. The differences between Phenotypic Coefficients of Variation and Genotypic Coefficients of Variation were not particularly noticeable in the experimental material used currently. The majority of the measured traits showed high heritability, highlighting their stability over time. PCA utilized for quantitative morphological features, the first two principal components collectively accounted for more than 86.8% of the phenotypic variation. Subsequently, a dendrogram was constructed, which clustered breeding and parental populations into three distinct groups. The 15 SCoT markers produced a total of 164 extended fragments, with 139 (85%) of them showed polymorphic.The genetic similarity between the populations exhibited a range of 0.08–0.81, and cluster analysis utilizing Jaccard similarity coefficients and the Unweighted Pair Group Method with Arithmetic Mean (UPGMA) technique revealed clear distinctions among the three breeding populations and their parental populations. Altogether, the findings indicate that morphological DUS descriptors effectively distinguish some the populations, while others with overlapping expressions cannot be discriminated. Notably, SCoT markers demonstrate a fine ability to detect distinctions among fennel populations, suggesting the possibility of utilizing them as a complement to morphological traits in the DUS test. As a conclusion, these three newly breeding populations of fennel are distinct from each other and from their parental populations, and they can advance for registration and seed purity testing.

Processing and post-processing of fish skin as a novel material in tissue engineering - Ali Esmaeili; Azam Rahimi; Amin Abbasi; Behnam Hasannejad-Asl; Saeid Bagheri-Mohammadi; Mohammad Farjami; Saeed Heidari Keshel (Tissue and Cell, 2023)

Contribution of NOS3AS Variants to Susceptibility to Essential Hypertension: A Study in Kermanshah Province, Western Iran - Bahareh Karami; Azam Azimi; Zohreh Rahimi; Sousan Mahmoudi; Nazanin Jalilian (Biochemical Genetics, 2023)

Gene expression study of host-human T-cell leukaemia virus type 1 (HTLV-1) interactions: adult T-cell leukaemia/lymphoma (ATLL) - Masooma Rahimzada; Mehri Nahavandi; Mona Saffari; Azam Shafaei; Arman Mosavat; Sanaz Ahmadi Gezeldasht; Nazila Ariaee; Narges Valizadeh; Hossein Rahimi; Seyed Abdolrahim Rezaee; Mohammad Derakhshan (Molecular Biology Reports, 2023)

Phosphate-Solubilizing Bacteria Modulated Salinity Stress in the Presence of Phosphorous through Improving Growth, Biochemical Properties, and Gene Expression of Chickpea (Cicer arientnum L.) - Azam Rahimi Chegeni; Foad Fatehi; Asa Ebrahimi; Mahmood Maleki (Journal of Soil Science and Plant Nutrition, 2023)

A new cryotop vial device system provides an aseptic cryoprotectant-free and centrifuge-free cryopreservation of human spermatozoa (a closed system) - Narges Bagheripour; Mohammad Ali Khalili; Ali Nabi; Maryam Mahaldashtian; Serajoddin Vahidi; Azam Agha-Rahimi (Cryobiology, 2023)

Oxidative Stress Parameters, Trace Elements, and Lipid Profile in Iranian Patients with Gaucher Disease - Hadi Mozafari; Shohreh Khatami; Amir Kiani; Zohreh Rahimi; Asad Vaisi-Raygani; Azam Afsharnaderi; Mohammad Reza Alaei (Biological Trace Element Research, 2020)

Development and diversity of a novel panel of short tandem repeat markers encompassing the SCN5A gene in Iranian population - Zahra Zafari; Azam Amirian; Faezeh Rahimi Nejad; Vahid Akbari; Mohammad Taghi Akbari; Sirus Zeinali (Journal of Genetics, 2018)